First measurement of quarkonium polarization in nuclear collisions at the LHC - Acharya, Shreyasi; Leardini, Lucia; López, Jorge; Martin, Nicole Alice; Ohlson, Alice; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; Schmah, Alexander; Schmidt, Marten Ole; Stachel, Johanna; Stiefelmaier, Stephan; et al. (Physics letters, 2021)
The polarization of inclusive J/ψ and ϒ(1S) produced in Pb-Pb collisions at sNN=5.02 TeV at the LHC is measured with the ALICE detector. The study is carried out by reconstructing the quarkonium through its decay to muon pairs in the rapidity region 2.5<y<4 and measuring the polar and azimuthal angular distributions of the muons. The polarization parameters λθ, λϕ and λθϕ are measured in the helicity and Collins-Soper reference frames, in the transverse momentum interval 2<pT<10 GeV/c and pT<15 GeV/c for the J/ψ and ϒ(1S), respectively. The polarization parameters for the J/ψ are found to be compatible with zero, within a maximum of about two standard deviations at low pT, for both reference frames and over the whole pT range. The values are compared with the corresponding results obtained for pp collisions at s=7 and 8 TeV in a similar kinematic region by the ALICE and LHCb experiments. Although with much larger uncertainties, the polarization parameters for ϒ(1S) production in Pb-Pb collisions are also consistent with zero.